Awareness of Basic Life Support among Health Personnel in a Rural Teaching Hospital - Giri, Prabin Kumar; Pokhrel, Bishal; Panta, Prem Prasad; Khapung, Robin (Journal of Karnali Academy of Health Sciences, 2020)
Background: Cardiopulmonary resuscitation success rates depend on the knowledge and skills of Adult basic life support (BLS) and advanced life support. The objective of the study was to find the level of awareness on BLS and skills among health personnel working in different departments of a rural teaching hospital. Methods: This descriptive cross-sectional study was conducted in a tertiary care hospital of Karnali Academy of Health Sciences, Jumla, Nepal. The awareness level about BLS was assessed using a structured questionnaire. Health personnel’s previous exposure to BLS and the inclusion of BLS in their curriculum was also assessed. Results: Among 91 participants,74% (n=67) heard about BLS ,64% (n=58)have seen performing and 25%(n=23) have performed CPR. Only 8%(n=7) attended a workshop on BLS. 43% (n=39) answered 100 and 46%(n=42) answered 30 compression per minute in adult during CPR.71%(n=65) knew the ratio of chest compression to breath in adults. Only 41%(n=37) identified anatomy/area mid-chest for chest compression. Only 40%(n=36) are familiar to the Heimlich maneuver and 5.5%(n=5) were aware of the sequence of BLS which is Head tilt, chin lift, check the pulse. Seventy-eight percent (n=71) responded that BLS training should be a part of the medical curriculum. Mean awareness of general medicine is significantly lower than the other two groups (P<0.001). Conclusion: The level of awareness and knowledge regarding BLS is different among health personnel. Hospital staff and nursing students had better knowledge regarding BLS than general medicine students.